When is the risk of cooperation worth taking? The prisoner's dilemma as a game of multiple motives - Christoph Engel; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2013)
Both in the field and in the lab, participants frequently cooperate, despite the fact that the situation can be modelled as a simultaneous, symmetric prisoner's dilemma. This experiment manipulates the payoff in case both players defect, and explains the degree of cooperation by a combination of five motives: the size of gains from cooperation, expectations about cooperativeness in the population in question, the degree of risk and loss aversion, and the degree by which a participant is tempted to inflict harm on another participant if this gives her a chance for an even higher payoff. Information about these motivational forces stems from additional within subjects tests. All five factors are significant only if one controls for all the other motives, which suggests that a prisoner's dilemma is a game jointly characterised by these five motives. The need to control for the remaining explanations seems to be the reason why earlier attempts at explaining choices in the prisoner's dilemma with personality have not been successful.
Keywords: H41; C72; C91; D03; 330; efficiency; Risk aversion; Conditional Cooperation; prisoner's dilemma; Belief; Loss Aversion; Risky Dictator Game; Gefangenendilemma; Kooperation; Motivation; Test